Determination of beam characteristics by its vibration measurement - Menh, Nguyen Cao; Toan, Tran Trong (Vietnam Journal of Mechanics, 1995)
On the basis of analyzing the transverse vibration of a clamped-free beam, in this paper an inverse problem is investigated. The analytical method· and computational program me have been presented for determination of the length of the beam when vibrations at some points on the beam with external distribution excitation or vibration at one point with some excited frequencies are measured. The obtained results from the illustration examples described in the paper give us the procedure for selecting one solution in multi-solution inverse problem.